PARTYPASSIVE MODEL OF STRATEGIC PLANNING AT LEVEL OF LOCAL SELF-GOVERNMENT - Moroz , Olena; Herasymchuk, Viktoriya; Skrebcova, Kseniya (Theory and Practice of Public Administration, 2019)
The authors indicate the effectiveness of introducing a participatory model of strategic development of local self-government as a tool to ensure its capacity. It is determined that strategic planning of local self-government development involves involvement in the work on a strategic document of a wide representation of the local environment (representatives of the main strata of the city, executive authorities, public organizations, business sector), whose activities are aimed at determining: the future image (vision) of the city, the main (strategic) goals that will achieve the acquisition of a community-defined city; action plans, that is, logical sequential actions aimed at achieving these objectives through the use of specific procedures.The purpose of the work is to substantiate theoretical foundations and to substantiate practical recommendations for building a participatory model of strategic development at the level of local self-government.In the conditions of the present successful method of strategy development, in which three are the subjects of the national economy - the authorities, business and the public must jointly, by consensus, create a common strategy of socio-economic development of the territory of the region as a set of strategic goals that are combined into an action program based on identified internal advantages and disadvantages of socio-economic economic system, available resources, opportunities and threats to the external environment. The article identifies that one of the most effective tools of effective city management is the development of a participatory model of its strategic development, which is an effective tool in solving common problems of residents and the implementation of basic tasks in terms of capacity, economic growth, increasing investment attractiveness, quality of life in the community through effective use of resources and realization of common interests of authorities, community and business.